Oral Lesions in Elderly Patients in Referral Centers for Oral Lesions of Bahia - Souza, Sarah; Alves, Técia; Santos, Jean; Oliveira, Márcio (International Archives of Otorhinolaryngology, 2015)
Introduction The aging population phenomenon is occurring on a global scale; aging affects all of the structures of organisms, including the oral cavity.Objective To estimate the frequency of oral lesions, according to the clinical and histopathologic diagnoses, and to describe the sociodemographic profile of the elderly treated at the referral centers of oral lesions of public universities in Bahia, Brazil.Methods A descriptive epidemiologic study with transverse characteristics was conducted with elderly patients between August 2010 and January 2012. A form was used to collect data. The descriptive analysis consisted of calculating the simple and relative frequencies of sociodemographic variables and oral lesions.Results The population was predominantly black women, and the minority of elderly people were retired. Fibroid (13%) and squamous cell carcinoma (145%) were more prevalent clinical diagnoses, with squamous cell carcinoma (30.7%) and fibrous hyperplasia more prevalent histopathologic diagnoses.Conclusion A prevention policy needs to be implemented to reduce new cases of oral lesions in Bahia, Brazil and to aid in early diagnosis and appropriate treatment of oral lesions.
Keywords: epidemiology; mouth diseases; elderly; mouth mucosa; oral lesions; diagnosis oral